2021
DOI: 10.1186/s13287-021-02618-w
|View full text |Cite
|
Sign up to set email alerts
|

SUMO1 modification of IGF-1R combining with SNAI2 inhibited osteogenic differentiation of PDLSCs stimulated by high glucose

Abstract: Background Periodontal disease, an oral disease characterized by loss of alveolar bone and progressive teeth loss, is the sixth major complication of diabetes. It is spreading worldwide as it is difficult to be cured. The insulin-like growth factor 1 receptor (IGF-1R) plays an important role in regulating functional impairment associated with diabetes. However, it is unclear whether IGF-1R expression in periodontal tissue is related to alveolar bone destruction in diabetic patients. SUMO modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…However, high glucose-induced damage to PDLSCs presents a major challenge to their applications in diabetic individuals [16]. Accumulating evidence indicates that PDLSCs incubated in high glucose exhibit impaired stem cell performance, including reduced proliferation and multilineage differentiation potentials, which would compromise the therapeutic effect of these cells [17,18]. Therefore, enhancing the stemness of PDLSCs under high glucose is important for periodontal tissue regeneration in diabetic individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, high glucose-induced damage to PDLSCs presents a major challenge to their applications in diabetic individuals [16]. Accumulating evidence indicates that PDLSCs incubated in high glucose exhibit impaired stem cell performance, including reduced proliferation and multilineage differentiation potentials, which would compromise the therapeutic effect of these cells [17,18]. Therefore, enhancing the stemness of PDLSCs under high glucose is important for periodontal tissue regeneration in diabetic individuals.…”
Section: Introductionmentioning
confidence: 99%
“…IGF1R glucose-induced osteogenic differentiation of PDLCs. 43 Through downstream targets, IGF1R regulates several signaling pathways, such as PI3K/AKT, 44 RAS/RAF/ERK 45 and STAT3 signaling pathways. 46 Intriguingly, it has been reported that the IGF1R/PI3K/AKT axis positively regulates Notch ligand-induced activation of Notch signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [ 45 ] found that high glucose induced SUMOylation of Smad4 via SUMO2/3 and activated TGF-β/Smad signaling in mesangial cells. SUMOylation of IGF-1R in periodontal ligament stem cells cultured in high glucose medium inhibited osteogenic differentiation [ 46 ]. Lysine 2806 is an important site for ATBF1 SUMOylation, whose mutation prevents MDA-MB-231 cells from forming tumors in nude mice [ 21 ].…”
Section: Discussionmentioning
confidence: 99%